System-level fault diagnosis in fixed topology mobile ad hoc networks. (1st January 2013) - Sahoo, Manmath Narayan; Khilar, Pabitra Mohan
In this paper, we present a protocol for diagnosing faulty mobiles using asymmetric comparison-based approach that exploits the shared nature of communication in mobile ad hoc networks (MANETs). The protocol is divided into three main phases: a Testing_Responding phase, a Gathering phase and a Building_Disseminating phase. During the Testing_Responding phase, units can test their neighbours and also respond to the received test messages. In the Gathering phase, units collect and compare the responses from their neighbours to generate local diagnosis views. A spanning tree is constructed in Building_Disseminating phase that covers all fault free active mobiles in the system and is used to exchange the local diagnosis information those are compounded to generate a global diagnosis view of the whole system. We consider both hard and soft faulted mobile hosts. The proposed protocol is shown to have less communication complexity and hence well suited for energy constrained MANETs.